Nursing and worker’s health: research group analysis - Marluce Rodrigues Godinho; Rosângela Maria Greco; Ângela Maria Corrêa Gonçalves (Rev Rene)
Occupational Health is an area of Public Health that has been studied since ancient times. The present study consists of a documental quantitative analysis research that aimed to analyze and discuss the research groups in Brazil aimed at the worker’s health, particularly nursing. Performed by accessing the site directory of research groups of the National Council of Scientific and Technological Development, it resulted in the identification of 188 groups, 41of which were from the nursing area. The analysis revealed a significant concentration in the Southeast region of the country and most researchers were female, with expressive participation of students. The themes addressed in the groups were: working conditions, ergonomics, mental health, safety and quality of life of workers. They show that the concern about health problems from work has been researched aiming the improvement of workers’ health care.